2020
DOI: 10.1101/2020.05.07.082925
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

A Combined approach of MALDI-TOF Mass Spectrometry and multivariate analysis as a potential tool for the detection of SARS-CoV-2 virus in nasopharyngeal swabs

Abstract: Coronavirus disease 2019 is caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). The rapid, sensitive and specific diagnosis of SARS-CoV-2 by fast and unambiguous testing is widely recognized to be critical in responding to the ongoing outbreak. Since the current testing capacity of RT-PCR-based methods is being challenged due to the extraordinary demand of supplies, such as RNA extraction kits and PCR reagents worldwide, alternative and/or complementary testing assays should be develop… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(14 citation statements)
references
References 11 publications
3
11
0
Order By: Relevance
“…Natchigall et al [13] reported in nasal swab samples that five of the seven peaks, distinguishing Cov+ and Cov-groups, have a higher intensity distribution in healthy individuals. Similarly, in another study using swab samples, all the discriminant peaks possessed a higher intensity distribution for uninfected individuals than for SARS-CoV-2 contaminated patients [14]. Conversely, here, in saliva samples, discriminant MS peaks correspond mainly to up-regulation protein expression subsequent to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 49%
See 1 more Smart Citation
“…Natchigall et al [13] reported in nasal swab samples that five of the seven peaks, distinguishing Cov+ and Cov-groups, have a higher intensity distribution in healthy individuals. Similarly, in another study using swab samples, all the discriminant peaks possessed a higher intensity distribution for uninfected individuals than for SARS-CoV-2 contaminated patients [14]. Conversely, here, in saliva samples, discriminant MS peaks correspond mainly to up-regulation protein expression subsequent to SARS-CoV-2 infection.…”
Section: Discussionsupporting
confidence: 49%
“…Another work has shown that the combination of MALDI-TOF MS and machine learning (ML) analysis appears to be a suitable strategy for COVID-19 diagnosis using NPS specimens [14]. The application of this strategy to serum samples succeeded to classify COVID-19 patients according to the severity of clinical symptoms [15].…”
Section: Introductionmentioning
confidence: 99%
“…If there is a lack of freezer facility for prior-collected gargle/saliva samples to perform RT-PCR examination, those are already known, and in that case, only prospective testing is possible. Several of the researchers are effortlessly working with numerous other researchers collecting gargle/saliva test samples and process as a demo where a PCR testing for selected swabs can be simultaneously processed ( Iles et al, 2020b ; Rocca et al, 2020 ). Such research groups have to analyze different samples also using their MALDI-ToF instrumentation with necessary reagents involved and by their all possible technical support.…”
Section: Emerging Serological Tests For Sars-cov-2mentioning
confidence: 99%
“… 45 Using MALDI-MS combined multivariate statistical analysis, Dattero et al showed the potential of MALDI-MS as a complementary diagnostic tool for discriminating SARS-CoV-2 from other viruses. 46 Overall, LC and MALDI-MS based proteomics has shown potential as a key COVID-19 research area; however, development of rapid and sensitive MS techniques along with trials in larger clinical studies are necessary to translate the beneficial aspects of MS-based proteomics in pandemics like COVID-19 disease ( Figure 1 ).…”
Section: Mass Spectrometry-based Proteomics In Covid-19mentioning
confidence: 99%